THE EFFECT OF TAXATION COUNSELING TO TAXPAYER AWARENESS LEVEL IN TAX SERVICE OFFICE ‘PRATAMA’ MANADO - Longdong, Natalia Angelia (Universitas Sam Ratulangi, 2015)
The changes of tax system from Official Assessment to Self Assessment, gives credence taxpayers to register, calculate, pay and report their own tax obligations. This study aimed to determine the effect of taxation counseling to taxpayer awareness level in Tax Service Office ‘Pratama’ Manado (KPP Pratama Manado). The method used in this research is descriptive research survey to determine the effect of taxation counseling to taxpayer awareness level in KPP Pratama Manado. The Multiple Linear Regression Analysis, used by the researcher to analyze the influence of independent variable to dependent variable. The survey result revealed the implementation of the taxation counseling does not affect taxpayer awareness level in the KPP Pratama Manado. Suggested to KPP Pratama Manado to provide the taxation counseling periodically to the whole society so increase awareness of paying taxes. Keywords: taxation counseling, taxpayer awareness level